Multiplexed target enrichment of coding and non-coding transcriptomes enables studying Candida spp. infections from human derived samples - Hovhannisyan, Hrant; Rodríguez, Antonio; Saus, Ester; Vaneechoutte, Mario; Gabaldón, Toni (Frontiers in Cellular and Infection Microbiology, 2023)
The study of transcriptomic interactions between host and pathogens in in vivo conditions is challenged by the low relative amounts of the pathogen RNA. Yeast opportunistic pathogens of the genus Candida can cause life-threatening systemic infections in immunocompromised patients, and are of growing medical concern. Four phylogenetically diverse species account for over 90% of Candida infections, and their specific interactions with various human tissues are still poorly understood. To enable in vivo transcriptomic analysis in these species, we designed and validated pan-Candida target capture probes to enrich protein-coding and non-coding transcriptomes. The probe-based enrichment approach outperformed enrichment based on differential lysis of host cells, and showed similar enrichment performance as an existing capture design, yet achieving better fidelity of expression levels, enabling species multiplexing and capturing of lncRNAs. In addition, we show that our probe-based enrichment strategy allows robust genotype-based identification of the infecting strain present in the sample.